(untitled) (Research, Society and Development, 2020)
This work describes the synthesis of CuBi2O4 material which, as reported in a literature work, presents photoactivity, behaving as a p-type material, having the ability to cleave the water molecule and reduce H + ions in hydrogen gas (H2 (g)). ), considered a renewable fuel source. The synthesis was done by the pyrolysis spray process, using an airbrush, a method that makes it possible to obtain thin and homogeneous films and then heat treatment, with different heating steps in one sample, and another simpler treatment in a second sample. After the synthesis and heat treatment process, the structural characterization was made using x-ray diffraction, revealing a single phase system. Scanning electron microscopy revealing the morphology caused by the different heat treatments. Cyclic Voltammetry, to show the material response when exposed to light, and what current density each heat treatment resulted in. Chronoamperometry serving as the basis for showing plate stability when subjected to resistance tests over time, and hydrogen quantification. Thus, the main objective of this work is to show the structural changes resulting from the heat treatment.